Effects of Stereoisomerism on the Crystallization Behavior and Optoelectrical Properties of Conjugated Molecules. (11th April 2013) - Liu, Jianhua; Zhang, Yuan; Phan, Hung; Sharenko, Alexander; Moonsin, Preecha; Walker, Bright; Promarak, Vinich; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> Three stereoisomers of DPP(TBFu)2 are separated and identified to investigate the effects of stereoisomerism on crystal structures and the optoelectrical properties. The crystal structures and FET mobility are sensitive to stereoisomers, in which the mesomer possesses the highest carrier mobility and the greatest crystallization tendency to dominate the crystallization in spin‐cast films of the as‐synthesized stereoisomeric mixture. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>